Electronic structure governs biological fate: Multi-scale computational nanotoxicology of TiO₂ nanoparticles across polymorphs, morphologies, and sizes - Valentín Diez-Cabanes; Sergio de-la-Huerta-Sainz; Alberto Gutierrez-Vega; Sonia Martel; Natalia Fernández-Pampín; Carlos Rumbo; Pedro A. Marcos; Alfredo Bol; Domenico Marson; Erik Laurini; Santiago Aparicio (NanoImpact, 2026)

MiRNAs and tempol therapeutic potential in prostate cancer: a preclinical approach - Isabela Maria Urra Rossetto; Letícia F. Alves; Leonardo A. Marson; Murilo V. Geraldo; Felipe R. Santos; Fábio Montico; Valéria H. A. Cagnon (Journal of Molecular Histology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Microcontaminants degradation in tertiary effluent by modified solar photo-Fenton process at neutral pH using organic iron complexes: Influence of the peroxide source and matrix composition - Ivo A. Ricardo; Eduardo O. Marson; Cleiseano E.S. Paniagua; Domingos Lusitâneo P. Macuvele; Maria Clara V.M. Starling; José Antonio Sánchez Pérez; Alam G. Trovó (Chemical Engineering Journal, 2024)

Drift bottle data hint at large-scale ocean circulation changes - Natasha A. Ridenour; Liam Buchart; Eddy Carmack; Inge Deschepper; Eric Galbraith; Geoff Green; Juliana M. Marson; Clark Pennelly; Tahya Weiss-Gibbons; Paul G. Myers (Frontiers in Marine Science, 2023)
Over the last two decades, in an effort to engage youth in polar science, the Students On Ice (SOI; https://studentsonice.com/ ) project has become a platform for youth to partake in scientific expeditions around the globe. Among the various activities offered, youth are able to join cruises in the North Atlantic or Arctic, and drop sealed glass bottles into the ocean. Of the thousands that have been deployed, 5% of bottles have been recovered and reported back to SOI with details on when and where they were found. Here, we compare the observational bottle data with virtual particle trajectories from a high resolution regional ocean model. Although modelling results indicate a higher likelihood of bottles reaching the shores of the western Atlantic, the majority of recovered bottles were found on the eastern side of the Atlantic. We attribute this disparity to differences in population density in Canada and Europe, biasing the recovery rates. Despite this bias, we find that changes in recovery locations over time are consistent with changes in the main ocean currents associated with the contraction and expansion of the North Atlantic Subpolar Gyre, as simulated in our ocean model. In 2007, a large number of bottles were found in Norway, coinciding with a contracted North Atlantic Subpolar Gyre during 2004-2008. While between 2012-2016, the majority of bottles were recovered on the British Isles, during a time of gyre expansion. These results underline the importance of large scale oceanic cycles for tracking marine debris and pollution, and show how even simple data collection methods, such as drift bottles, can provide clues to the changes in the large scale ocean circulation.

Performance of different peroxide sources and UV-C radiation for the degradation of microcontaminants in tertiary effluent from a municipal wastewater treatment plant - Edna A. Alberto; Gabrielly M. Santos; Eduardo O. Marson; Moisés J. Mbié; Cleiseano E.S. Paniagua; Ivo A. Ricardo; Maria Clara V.M. Starling; José Antonio Sánchez Pérez; Alam G. Trovó (Journal of Environmental Chemical Engineering, 2023)

LP-36: The Clariant CompTox Suite – Towards implementation of predictive toxicology approaches to support discovery of chemical alternatives that are safe and sustainable by design - Q. Li; K. Addis; D. Becker; L. Bodelon; K. Framesqui; M. Hufnagel; A. Marson; F.A. Grimm (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Degradation of Direct Red 81 mediated by Fenton reactions: multivariate optimization, effect of chloride and sulfate, and acute ecotoxicity assessment - Eduardo O. Marson; Vinícius A. B. de Paiva; Bárbara R. Gonçalves; Oswaldo Gomes Júnior; Waldomiro Borges Neto; Antonio E. H. Machado; Alam G. Trovó (Environmental Science and Pollution Research, 2017)

Evolution of the deep Atlantic water masses since the last glacial maximum based on a transient run of NCAR-CCSM3 - Juliana M. Marson; Lawrence A. Mysak; Mauricio M. Mata; Ilana Wainer (Climate Dynamics, 2016)

MRI volume of the medial frontal cortex predicts financial capacity in patients with mild Alzheimer’s disease - Luke E. Stoeckel; Christopher C. Stewart; H. Randall Griffith; Kristen Triebel; Ozioma C. Okonkwo; Jan A. den Hollander; Roy C. Martin; Katherine Belue; Jacquelynn N. Copeland; Lindy E. Harrell; John C. Brockington; David G. Clark; et al. (Brain Imaging and Behavior, 2013)

Xerombrophila crystallifera, a new genus and species in the Helotiales - Hans-Otto Baral; Guy Marson; Mesfin Bogale; Wendy A. Untereiner (Mycological Progress, 2013)

Brain Proton MRS is Correlated with Financial Abilities in Patients with Alzheimer’s Disease - H. Randall Griffith; Ozioma C. Okonkwo; Jan A. den Hollander; Katherine Belue; Sara Lanza; Lindy E. Harrell; John C. Brockington; David G. Clark; Daniel C. Marson (Brain Imaging and Behavior, 2007)